(untitled) (Nexo Revista Científica, 2024)
This document contains the analysis and results of the work carried out in the period 2024 as part of the research “ALTERNATIVE CEMENT-BASED MATERIALS” accredited by the UNI in collaboration with “Programa Delfín”, the University of Guadalajara and the Universidad Veracruzana, allowing the analysis and exploration of possibilities for using alternative concretes with cement and recycled glass (dark and light). The results compared with other similar studies and supported by the regulations for their preparation and testing, demonstrated the viability of these materials for use in concrete products for non-structural purposes, so that the importance and contribution to the sustainability of the materials is proven. processes and resources. Starting from the waste generated by the population in the constant use and disposal of glass, a proposal for recycled concrete was developed from reuse with the replacement of a percentage of the fine aggregate with recycled glass, these materials being crushed and sieved and proposing a dosage based on similar studies.